New Insights into Acquisition, Boosting, and Longevity of Immunity to Malaria in Pregnant Women - Fowkes, Freya Jl; McGready, Rose; Cross, Nadia J.; Hommel, Mirja; Simpson, Julie A.; Elliott, Salenna R.; Richards, Jack S.; Lackovic, Kurt; Viladpai-Nguen, Jacher; Narum, David; Tsuboi, Takafumi; Anders, Robin F.; et al. (The Journal of infectious diseases, 2012)
Background. How antimalarial antibodies are acquired and maintained during pregnancy and boosted after reinfection with Plasmodium falciparum and Plasmodium vivax is unknown. Methods. A nested case-control study of 467 pregnant women (136 Plasmodium-infected cases and 331 uninfected control subjects) in northwestern Thailand was conducted. Antibody levels to P. falciparum and P. vivax merozoite antigens and the pregnancy-specific PƒVAR2CSA antigen were determined at enrollment (median 10 weeks gestation) and throughout pregnancy until delivery. Results. Antibodies to P. falciparum and P. vivax were highly variable over time, and maintenance of high levels of antimalarial antibodies involved highly dynamic responses resulting from intermittent exposure to infection. There was evidence of boosting with each successive infection for P. falciparum responses, suggesting the presence of immunological memory. However, the half-lives of Plasmodium antibody responses were relatively short, compared with measles (457 years), and much shorter for merozoite responses (0.8-7.6 years), compared with PƒVAR2CSA responses (36-157 years). The longer half-life of antibodies to PƒVAR2CSA suggests that antibodies acquired in one pregnancy may be maintained to protect subsequent pregnancies. Conclusions. These findings may have important practical implications for predicting the duration of vaccine-induced responses by candidate antigens and supports the development of malaria vaccines to protect pregnant women.